Urban schools : crisis and revolution - Deneen, James R. (Rowman & Littlefield Education, 2011)
Urban Schools: Crisis and Revolution describes America's inner-city public schools and the failure of most to provide even a minimally adequate education for their students. With numerous examples, James Deneen and Carm Catanese argue that these failures are preventable. Early chapters document the two-tiered character of American public schools, the tragic consequences of failing schools for millions of students-mostly Black and Hispanic-and the financial costs to American society. In later chapters, Deneen and Catanese describe the special problems of inner-city schools and the changes in.